De la procrastination scolaire à la flexibilité psychologique : : considérations empiriques, théoriques et cliniques - Plouffe, Natan; Dionne, Frédérick; Côté, Guylaine (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
The acceptance and commitment therapy (ACT) model is a promising approach in conceptualizing academic procrastination. It is also relevant to study the efficacy of ACT’s interventions on academic procrastination and to gain a better understanding of the mechanisms involved in this problem. This article has three aims: 1) to present new approaches in treating academic procrastination among university students, 2) to review the present state of knowledge of academic procrastination from an ACT perspective and 3) to propose a new intervention protocol based on ACT for academic procrastination. Keywords: academic procrastination, acceptance and commitment therapy (ACT), psychological flexibility, cognitive and behavioural therapy (CBT)